A MODEL SUGGESTION FOR CASH CONVERSION OF INVENTORYAND BASEMENT OF MODEL FINANCIAL RATIOS ANALYSIS - Pazarceviren, Selim Yuksel; Ozsuer, Ugur; Dede, Bayram (European Scientific Journal, ESJ, 2015)
Companies are trying to compete with each other with different management techniques such as cost management, sales management etc. Financial analysis is a very important tool for companies in measuring efficiency, measuring the degree of success, and in measuring the determination of companies’ target and cost volume. Although companies focus on cost management, they do not consider financial ratio analysis on the same platform. Traditionally, companies usually consider material costs. However, the aim of this study is to give vision beyond the material costs according to the financial statement ratio analysis. We aimed at looking at material costs as a finished cost with their performance result. Thus, it will give a more competitive power to companies. Also, we considered to see through analytical liquidity analysis simulation tables, material costs cash collection and their effects on financial ratios. In addition, we analyzed the current assets cash flow and cash balance and their effects. On the other hand, we aim to simulate with different current assets, scenarios effects on companies’ financial structure and cash balances through this model. Consequently, we aim to make risk analysis (risk simulation) for different current assets scenarios. Thus, this is done in order to simulate effects on companies’ financial structure and cash balance.